0732 Evaluation of Uvulopalatopharyngoplasty as a Treatment of Obstructive Sleep Apnea in Non-obese and Obese Children. (12th April 2019) - Gupta, Gita; Stanley, Jeffrey; Hassan, Fauziya
Abstract: Introduction: Adenotonsillectomy (T&A) is the first line treatment for children with obstructive sleep apnea (OSA). Positive airway pressure and oxygen are often utilized when OSA persists. For some children, tolerance to these therapies can be difficult. Limited studies exist of other interventions such as uvulopalatopharyngoplasty (UPPP) in children. In addition to crowded upper airway anatomy, obesity is a known risk factor for OSA. Objective: Evaluate the improvement in OSA severity and sleep architecture following UPPP in obese and non-obese children with T&A. Methods: Retrospective chart review of pre- and post-operative in laboratory polysomnograms (PSG) of thirty-three children with history of previous T&A aged 1 to 17 years who underwent UPPP between 2000 and 2016 was performed. Many children had underlying chronic medical conditions such as cerebral palsy. We assessed apnea hypopnea index (AHI), Obstructive Apnea Hypopnea Index (OAHI), in addition to percentage of slow wave sleep and rapid eye movement (REM) sleep prior to and after UPPP. Results: Overall, children demonstrated improvement in AHI after UPPP and previous T&A {17.0 (SD-18.1) to 11.8, (SD-18.1)}. AHI decreased in both non-obese {17.7 (SD 19.4) to 12.7 (SD 20.2)}, and among obese children {14.8 (SD 15.1) to 8.9 (SD 9.0)}. OAHI also improved after surgery among both the non-obese {16.7 (SD 19.0) to 11.5 (SD 19.9)} and in the obese group {13.1 (SD 13.5) to 7.3 (SD 8.0) with greater change noted among obese children. A similar increase in Stage N3 sleep was noted after UPPP in non-obese {35.3 (SD 22.5) to 38.9 (SD 23.7)} and obese {28.9 (SD 16.3) to 31.9(SD 14.9)} groups of children. Due to the small sample size, these trends were not of statistical significance. Conclusion: UPPP in children with previous T&A is potential adjunctive treatment for obstructive sleep apnea. Further study with a higher-powered sample may provide further insight into this treatment option. Support (If Any): Nothing to disclose